Urinary DNA adductomics – A novel approach for exposomics - Marcus S. Cooke; Chiung-Wen Hu; Yuan-Jhe Chang; Mu-Rong Chao (Environment International, 2018)
The exposome is a concept that encompasses the totality of internal and external environmental exposures, from conception onwards. Evaluation of the exposome, across the lifecourse represents a significant challenge, e.g., methods/technology may simply not exist to comprehensively assess all exposures, or they may not be applicable to human populations, or may have insufficient sensitivity. Cellular DNA adductomics aims to determine the totality of DNA adducts in the cellular genome. However, application to human populations requires the necessarily invasive sampling of tissue, to obtain sufficient DNA for sensitive analysis, which can represent a logistical and IRB challenge, particularly when investigating vulnerable populations. To circumvent this, we recently applied DNA adductomics to urine, detecting a range of expected and unexpected 2′-deoxyribonucleoside DNA adducts. However, base excision repair, the main DNA repair pathway for non-bulky DNA adducts, and processes such as spontaneous depurination, generate nucleobase adducts. Herein we propose a strategy to simultaneously assess 2′-deoxyribonucleoside and nucleobase adducts, using a widely used mass spectrometic platform (i.e., triple quadrupole tandem mass spectrometry). This will provide a much needed DNA adductomic approach for non-invasively, biomonitoring environmental exposures, through assessing the totality of DNA adducts; contributing to the evaluation of the exposome, across the life-course. Keywords: Adductomics, Exposome, DNA damage, Environmental exposure, DNA repair, Mass spectrometry